Association between Receipt of Assistance Accessing Social Programs and Experience of Care for Health Center Patients. (20th August 2020) - Nguyen, K.; Trivedi, A.; Cole, M.
Abstract : Many community health centers (CHCs), which deliver comprehensive primary care services to over 28 million low‐income patients irrespective of ability to pay, systematically screen for and facilitate patients' access to social services or basic needs. The extent to which patients receive such assistance varies widely across CHCs. We examined the degree to which CHC patients report receiving assistance with accessing social programs and basic needs and compared measures of access and quality between patients who received assistance relative to similar patients who did not. We used the 2014‐15 Health Center Patient Survey, a cross‐sectional survey collected by the Health Resources and Services, and the first and only patient‐level data to be collected post‐Affordable Care Act that is representative of all CHC patients. We defined our exposure, having "received CHC assistance, " based on whether a patient received any health center assistance accessing social programs (e.g., applying for government benefits) or basic needs (e.g., transportation, housing, employment, obtaining food, and obtaining clothes). Our outcomes were reporting a CHC as a usual source of care, reporting the ED as a usual source of care, having a routine checkup in the last year, perceived quality of care, and willingness to recommend the CHC to family and friends. We calculated inverse probability of treatment weights (IPTWs), using propensity scores, to balance on observable characteristics between patients who received CHC assistance versus those who did not. Scores included 21 patient‐level sociodemographic and clinical characteristics. We used doubly robust logistic regression models with IPTWs to compare outcomes for patients who received CHC assistance to similar patients who did not and calculated adjusted differences. 4, 699 adults age 18‐64, representing 12.6 million patients nationwide, who received care at CHCs. Principal Findings: About 36% of our sample reported receiving CHC assistance, which included applying for government benefits (25.2%), transportation (12.6%), or obtaining food (5.5%). Relative to statistically similar patients who did not, patients who received CHC assistance to were significantly more likely to report a health center as their usual source of care (Odds Ratio[OR] = 1.82, adjusted difference = 8.2, P  < 0.01), more likely to report perceived quality of care as "the best" (OR = 1.79, adjusted difference = 9.8, P  < 0.01), and more likely to definitely recommend the CHC to family and friends (OR = 1.89, adjusted difference = 6.7, P  < 0.01). They were significantly less likely to report an ED as their usual source of care (OR = 0.47, adjusted difference = ‐3.5, P  < 0.01). Receiving CHC assistance with accessing social programs and meeting basic needs was associated with improved access to and quality of care. Proposed care delivery models that require systematic screening for patients' unmet social needs and connecting patients with social services could have several benefits, including improved care continuity and reduced reliance on the ED. This study may also provide evidence about the value of investing in additional eligibility assistance and outreach staff. More broadly, policies that decrease CHC revenue or roll back Medicaid eligibility may negatively affect CHC ability to connect patients to social services and compromise access to and quality of care. The Robert Wood Johnson Foundation.